Estrategias metodológicas de aprendizaje para la producción de bolsos y su incidencia en el rendimiento de los Estudiantes de Básica Superior de la Unidad Educativa ocho de noviembre de la Parroquia Balzapamba Provincia de Bolívar. - López Rivera, María Isabel (2018)
The purpose of this research work was to analyze everything related to the production of handbags, with the purpose of promoting methodological strategies for student learning and, in turn, to motivate them, the production of banana stem bags, interest them to these students, with the purpose of being able to start their own business, because this will consist of economic resources that will facilitate their living conditions and in turn to have their own micro business, this project interests them because it will help them since they had the idea of starting their own business, they realized that they almost did not recycle the stem of the banana at home much less in their school, they decided to apply beginning to take into account that it is very good to collect the stem with the purpose of being able to make crafts, this favored a lot the relations between students and teacher will improve their quality of life and generate sources of down sustainable and sustainable and be useful to society The purpose of this research work was to analyze everything related to the production of handbags, with the purpose of promoting methodological strategies for student learning and, in turn, to motivate them, the production of banana stem bags, interest them to these students, with the purpose of being able to start their own business, because this will consist of economic resources that will facilitate their living conditions and in turn to have their own micro business, this project interests them because it will help them since they had the idea of starting their own business, they realized that they almost did not recycle the stem of the banana at home much less in their school, they decided to apply beginning to take into account that it is very good to collect the stem with the purpose of being able to make crafts, this favored a lot the relations between students and teacher will improve their quality of life and generate sources of down sustainable and sustainable and be useful to society